Spectrum Sensing Using Energy Detector in Rayleigh Fading Channel - Patil Hemlata; Nekkanti Sai Vennela; Negi Disha; Masanagi Nikita; More Sakshi (ITM Web of Conferences, 2020)
Cognitive Radio, which is an adaptive and intelligent radio has an important feature called spectrum sensing. It monitors the presence or absence of the authorized users in a fixed or licensed spectrum. There is a rise in the use of wireless communications in recent times, which has led to the underutilization of the available bandwidth. This problem can be solved to some extent by using cognitive radio technology. Cognitive radio gives an opportunity for unauthorized users to use the licensed spectrum, resourcefully, when not in use. Using spectrum sensing energy detection methods, the existence of authorized users, in various fading channels can be done. The operating characteristics of the receiver can be analyzed using parameters of performance like signal to noise ratio, probability of false-alarm, probability of detection. In this paper we assess Rayleigh fading channel and compare with AWGN (non- fading) channel. Theoretical and simulated results are compared, and observations are being made.